Non-performing loans in Baltic States: determinants and macroeconomic effects - Jordan Kjosevski; Mihail Petkovski (Baltic Journal of Economics, 2017)
This study analyses the linkages between macroeconomic and bank-specific determinants of non-performing loans (NPLs) and their impact on macroeconomic performance in the Baltic States using two complementary approaches. First, we examine the macroeconomic and bank-specific determinants of NPLs for a panel of 27 banks from the Baltics using annual data for the period 2005–2014. The most important macroeconomic factors are GDP growth, inflation and domestic credit to the private sector. As for the bank-specific determinants, we found that the equity to total assets ratio, return on assets, the return on equity and the growth of gross loans were of importance. Second, we investigate the feedback between NPLs and its macroeconomic determinants. The results suggest that the real economy responds to NPLs and that there are strong feedback effects from macroeconomic conditions such as domestic credit to private sector, GDP growth, unemployment and inflation to NPLs.
Keywords: 330; Non-performing loans; macroeconomic determinants; bank-specific determinants; Baltic States; GMM difference; panel vector autoregressive model